Cold atmospheric pressure (CAP) plasma assisted tailoring of LDPE film surfaces for enhancement of adhesive and cytocompatible properties: Influence of operating parameters. (August 2016) - Pandiyaraj, K. Navaneetha; RamKumar, M.C.; Arun Kumar, A.; Padmanabhan, P.V.A.; Deshmukh, R.R.; Bendavid, Avi; Su, Pi-Guey; Sachdev, Abhay; Gopinath, P.
Abstract: Low density polyethylene (LDPE) plays a vital role in tissue engineering application because of its superior bulk properties. However, the cell affinity is one of the significant factors in determining the cell compatibility of polymers which depends on the surface properties such as hydrophilicity, surface chemistry and morphology. Due to intrinsic poor surface properties, the cell affinity is one of the major deterrents of LDPE films in biomedical applications. Hence, in the present investigation we discuss the influence of operating parameters such as applied potential, exposure time and type of plasma processing gases on the improvement of surface and cell compatible properties of the LDPE film using cold atmospheric pressure (CAP) plasma. The surface chemistry and hydrophilicity of the LDPE films were examined using X-ray photoelectron spectroscopy (XPS), contact angle (CA) respectively. Further, surface energy (SE) of the LDPE films were estimated from CA data by Fowke's approximation method. The quantification of topographical changes on the surface of LDPE films was carried out by atomic force microscopy (AFM). Adhesive strength of the surface modified films was analyzed by T-peel and lap shear tests. Finally, in vitro cytocompatibility studies of the surface modified LDPE films were carried out using NIH3T3 (mouse embryonic fibroblast) cells. The results obtained from various characterization techniques evidently revealed that CAP plasma treatment enhanced the surface properties (hydrophilicity, surface morphology and surface chemistry) of the LDPE films. These physico-chemical changes induced by the CAP plasma treatment facilitates the improvement in adhesive strength as well as adhesion and proliferation of cells on the surface of LDPE films. Highlights: Studied the influence of operating parameters of CAP plasma on the surface and cell compatible properties of LDPE films. Surface modified LDPE film exhibited significant physico-chemical changes which dependent on the operating parameters. The cell viability and adhesion to the surface modified films are enhanced markedly.